2019
DOI: 10.3389/fpls.2019.01384
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Central Carbon Metabolism in Apple Fruit Exposed to Postharvest Low-Oxygen Stress

Abstract: After harvest, fruit remain metabolically active and continue to ripen. The main goal of postharvest storage is to slow down the metabolic activity of the detached fruit. In many cases, this is accomplished by storing fruit at low temperature in combination with low oxygen (O2) and high carbon dioxide (CO2) partial pressures. However, altering the normal atmospheric conditions is not without any risk and can induce low-O2 stress. This review focuses on the central carbon metabolism of apple fruit during postha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 143 publications
(265 reference statements)
0
22
0
Order By: Relevance
“…For climacteric fruit like apples and tomatoes, the ripening process is characterized by a rise in respiration rate and ethylene production (Boeckx et al, 2019;Wills et al, 1998). In the present study, both the respiration rates of the 4°C-and −4°C-stored goji berry showed their F I G U R E 2 Effect of storage temperature on the respiration rate and ethylene (C 2 H 4 ) production rate of goji berry.…”
Section: Respiration Rate and C 2 H 4 Production Ratementioning
confidence: 99%
See 2 more Smart Citations
“…For climacteric fruit like apples and tomatoes, the ripening process is characterized by a rise in respiration rate and ethylene production (Boeckx et al, 2019;Wills et al, 1998). In the present study, both the respiration rates of the 4°C-and −4°C-stored goji berry showed their F I G U R E 2 Effect of storage temperature on the respiration rate and ethylene (C 2 H 4 ) production rate of goji berry.…”
Section: Respiration Rate and C 2 H 4 Production Ratementioning
confidence: 99%
“…The respiration rate of goji berries after harvest reached the peak on Day 4, and then generally declined, the pattern of which suggested that goji berry was typical of a climacteric fruit. The respiratory climacteric rise marks the end of active synthesis and the start of fruit senescence (Boeckx et al, 2019). While F I G U R E 3 Effect of storage temperature on fruit firmness and marketable fruit rate of goji berry F I G U R E 4 Effect of storage temperature on the contents of total soluble solids (TSS), total polysaccharides, flavonoids, and carotenoids of goji berry temperature has been identified as the most important external factor influencing the respiration rate of fresh horticultural products (Fonseca, Oliveira, & Brecht, 2002).…”
Section: Respiration Rate and C 2 H 4 Production Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Cytosolic hexoses are phosphorylated through the glycolytic pathway and split into triose phosphates, which are finally oxidized to pyruvate (Li et al, 2018). Pyruvate can then be transported into the matrix of the mitochondria by a mitochondrial pyruvate carrier to fuel the tricarboxylic acid (TCA) cycle (Li et al, 2018;Boeckx et al, 2019). Unrestricted availability of these soluble sugars is of critical importance for the maintenance of the fruit's respiratory metabolic functions, which are vital to producing energy, and assembling carbon-based compounds for use in various biosynthetic processes in primary and secondary metabolism (Boeckx et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have been conducted to better understand metabolic regulation in peach have primarily evaluated postharvest factors and cold storage disorders (Lauxmann et al, 2014;Bustamante et al, 2016;Tanou et al, 2017;Santin et al, 2018;2019;Monti et al, 2019;Lillo-Carmona et al, 2020), along with maturation/ripening physiology, environmental conditions and pest tolerance (Lombardo et al, 2011;Capitani et al, 2012;Monti et al, 2016;Karagiannis et al, 2016). Characterizing fruit metabolic shifts in response to preharvest factors is key to fruit quality improvement, as several of these compounds contribute to organoleptic characteristics that correlate with consumer preference.…”
Section: Introductionmentioning
confidence: 99%